2017
DOI: 10.1158/1535-7163.mct-17-0498
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine Promotes Autophagy and Apoptosis via TCRP1/Akt/mTOR Axis Inactivation in Human Hepatocellular Carcinoma

Abstract: Lycorine is a multifunctional bioactive compound, and it possesses potential anticancer activities. However, little is known about the underlying mechanism. In this research, we have found that lycorine significantly induces the apoptotic and autophagic capacities of hepatocellular carcinoma (HCC) cells in vitro and in vivo. Treatment with specific autophagy inhibitor (3-methyladenine/Bafilomycin A1) or knockdown of LC-3B/Atg5 by siRNA drastically enhances the apoptotic cell death effect by facilitating the sw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 49 publications
1
54
0
Order By: Relevance
“…Lycorine is extensively studied as an anti-tumour drug and has been demonstrated to have effects on the induction of cell apoptosis [72-77], autophagy [78] and cell cycle arrest [79, 80] in different tumour cell lines. Thus, in the present study, the toxicity of lycorine on endplate cells was carefully assessed, and we found that CEP cells showed no obvious apoptosis or cycle arrest effect at 0.4 µM LY, as this dose is much lower than the anti-tumour effect dose (4-50 µM) used in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lycorine is extensively studied as an anti-tumour drug and has been demonstrated to have effects on the induction of cell apoptosis [72-77], autophagy [78] and cell cycle arrest [79, 80] in different tumour cell lines. Thus, in the present study, the toxicity of lycorine on endplate cells was carefully assessed, and we found that CEP cells showed no obvious apoptosis or cycle arrest effect at 0.4 µM LY, as this dose is much lower than the anti-tumour effect dose (4-50 µM) used in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the above mention effects of lycorine, it can also modulate several signaling pathways to regulate growth and proliferation of cancer cells. These include the JNK pathway [69], the phosphor-Akt pathway [71,123], the MEK/ERK pathway [66] and the JAK/STAT signaling pathway [67].…”
Section: Inhibition Of Invasion and Metastasismentioning
confidence: 99%
“…Our previous studies have demonstrated that lycorine‐promoted autophagy and apoptosis inhibit the growth of HCC cells. Disruption of autophagy markedly enhances the apoptotic effect by facilitating the switch from autophagy to apoptosis, thus further augmenting antitumor effects . Therefore, the role of autophagy in cell survival and death is complex and may have diametrically opposed effects depending on the situation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) analysis was performed as reported above. 19 The prepared sections were incubated with anti-PARP, anti-p-Akt and anti-VIM antibodies overnight at 4 C, followed by biotin-conjugated secondary antibody. Images were obtained on a Leica DM4000B microscope (Leica, Wetzlar, Germany).…”
Section: Immunohistochemistry Assaymentioning
confidence: 99%
See 1 more Smart Citation